Impact of Coping Strategies on Health-Related Quality of Life in Young Adults with Multiple Sclerosis - Viviana Lo Buono; Francesco Corallo; Edoardo Sessa; Giangaetano D’Aleo; Carmela Rifici; Angelo Quartarone; Lilla Bonanno (Brain Sciences)
Multiple sclerosis (MS) is a chronic and progressive neurological disease that affects the central nervous system, resulting in a wide spectrum of cognitive, emotional, and physical deficits. The progressive course of MS poses significant challenges to patients and has a profound impact on health-related quality of life (HRQoL). The style of coping adopted plays a critical role in determining how individuals with MS adapt to and face the challenges of the disease and their overall well-being. This paper aims to examine the impact of coping strategies on HRQoL in young adults un-/minimally impaired (<5 years, EDSS ≤ 2.5) by MS (age 18–35 years). This retrospective cross-sectional cohort study included 98 young adults (33 males and 65 females) with relapsing–remitting MS who underwent neurological assessment using the Expanded Disability Status Scale. Participants completed the Italian version of the Multiple Sclerosis QoL-54 (MSQoL-54), which provides a physical and mental health score, and the Coping Orientation to Problems Experienced Inventory (Brief-COPE). The results showed a significant relationship between COPE scores and physical and mental health. Subjects affected by MS who tend to use more frequent coping strategies such as active planning, personal growth, and acceptance showed a better overall well-being and quality of life. These findings are relevant to clinical practice given the need to understand the coping variable to improve HRQoL. Understanding these relationships is crucial for developing effective interventions to enhance the well-being of MS subjects.